Desain Kuliah Agama Berbasis Digital - Ahmad Dahlan (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
human resource problems in Indonesia resulted from education that having low quality and uncompetitive in regional and international level. The problem more complex when commendation of APBN budget allocation, which is 20% for the education, cannot be fully realized. State College on Islamic Studies (STAIN) have to reconstruct themselves to find design and paradigm so that can produce alumnus which qualified, capable, and represent akhlakul karimah in implementing Islamic teaching that kafah (perfect). One of them is quality instructor resource that able to explore curriculum, that is based on competence. Curriculum that based on religion in the reality can be conducted with the availability of software programs, like The Holy Qur’an, Al-Kutub At-Tis’ah Li al-Hadits asy-Syarif, Maktabah At-Tafsir, Maktabah Al-Ushul al-Fiqh and others. These are several things to be aimed by STAIN /IAIN as part of their strategic plans. .